Reactivity, Mechanism, and Assembly of the Alternative Nitrogenases - Jasniewski, Andrew J; Lee, Chi Chung; Ribbe, Markus W; Hu, Yilin (Chemical reviews, 2020)
Biological nitrogen fixation is catalyzed by the enzyme nitrogenase, which facilitates the cleavage of the relatively inert triple bond of N2. Nitrogenase is most commonly associated with the molybdenum–iron cofactor called FeMoco or the M-cluster, and it has been the subject of extensive structural and spectroscopic characterization over the past 60 years. In the late 1980s and early 1990s, two “alternative nitrogenase” systems were discovered, isolated, and found to incorporate V or Fe in place of Mo. These systems are regulated by separate gene clusters; however, there is a high degree of structural and functional similarity between each nitrogenase. Limited studies with the V- and Fe-nitrogenases initially demonstrated that these enzymes were analogously active as the Mo-nitrogenase, but more recent investigations have found capabilities that are unique to the alternative systems. In this review, we will discuss the reactivity, biosynthetic, and mechanistic proposals for the alternative nitrogenases as well as their electronic and structural properties in comparison to the well-characterized Mo-dependent system. Studies over the past 10 years have been particularly fruitful, though key aspects about V- and Fe-nitrogenases remain unexplored.